Investigating fraction computation problem-solving among pre-service primary school teachers - Pramudiani, Puri; Alyani, Fitri; Dolk, Maarten; Widjaja, Wanty (Universitas Hamzanwadi, 2024)
The ability to solve problems involving fractions is a fundamental aspect of mathematics education. This study explores how Pre-Service Primary School Teachers approach problem-solving in fractional computations. A workbook is designed to support pre-service primary school teachers ' computational thinking in fraction-context challenges. The study employs a qualitative descriptive method encompassing interviews, study documentation, and observation to assess fraction computation problem-solving abilities. Twenty-seven participants were involved in this study. They were first-year students enrolled in the Primary School Teacher Education Department at one of the private universities in Jakarta, Indonesia. The findings reveal a notable outcome in pre-service primary school teachers ' understanding of fraction computation problem-solving, marked by recognizable strategies in their problem-solving approach. This research suggests that designing a series of workbooks containing various strategies in computational fractions and building a strong fractional number sense can help pre-service teachers reduce misconceptions and better understand fraction operations. These findings offer guidance for mathematics teacher education on how to effectively teach and embed the concept of fraction calculations to their future students so that they can only teach procedurally if they understand the meaning of fraction operations.